THE EFFECT OF THE COOPERATIVE SCRIPT MODEL ON READING ALOUND SKILLS IN THIRD GRADE STUDENTS OF SDN 001 PASAR BEU PANGEAN - Beti Anggela (Education Generation Journal, 2023)
This research is an experimental research with a Quasi Experimental Design research type. This type of experiment was carried out in two classes using a comparison class. The experimental design used in this study was a pretest posttest control group design with the aim of knowing the effect of the Cooperative Script learning model on nharing reading skills in third grade students of SDN 001 Pasar Baru Pangean. The number of students was 24 students who were divided into two groups, namely the experimental group and the control group. In this study, the technique of collecting data using a reading test on the Effect of Animals on Human Life, there are four aspects used in this study, namely fluency, accuracy, intonation, and punctuation. Based on the results of the study, the average score (mean) showed that the results of the pretest in the experimental group of class III students at SDN 001 Pasar Baru Pangean were 69.16 and in the control group was 68.75 and the average posttest results in the experimental group of SDN students 001 Pasar Baru Pangean is 74.58 and the control group is 69.58. The reading skills in class III SDN 001 Pasar Baru Pangean affect the aloud reading skills of third grade students at SDN 001 Pasar Baru Pangean by using a cooperative script model.   Key words: cooperative script model, aloud reading skills